Pengembangan Media Pembelajaran Pengenalan Pahlawan Nasional Sulawesi Utara Berbasis Augmented Reality - Nadya Verona Viani Kamasi; Stephanie Mariane Felly Nangoy (Universitas Bandar Lampung (UBL), 2023)
This research aims to develop a prototype of a learning media for the introduction of national heroes, specifically in the North Sulawesi Province, to help elementary school students gain a better understanding of national heroes, particularly in North Sulawesi. the study employs the Multimedia Development Life Cycle (MDLC) method, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. the final outcome of this research is the creation of an augmented reality-Based hero introduction application for a subject with the theme